2018
DOI: 10.1167/iovs.18-24096
|View full text |Cite
|
Sign up to set email alerts
|

RGC Neuroprotection Following Optic Nerve Trauma Mediated By Intranasal Delivery of Amnion Cell Secretome

Abstract: PurposeIntranasally delivered ST266, the biological, proteinaceous secretome of amnion-derived multipotent progenitor cells, reduces retinal ganglion cell (RGC) loss, optic nerve inflammation, and demyelination in experimental optic neuritis. This unique therapy and novel administration route delivers numerous cytokines and growth factors to the eye and optic nerve, suggesting a potential to also treat other optic neuropathies. Thus, ST266-mediated neuroprotection was examined following traumatic optic nerve i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 30 publications
(49 reference statements)
3
27
0
Order By: Relevance
“…The current studies demonstrated that intranasal delivery of the novel biologic therapy ST266 promoted beneficial effects on multiple features of experimental optic neuritis, including attenuating vision loss, promoting RGC survival, and reducing the degree of optic nerve inflammation and demyelination. Results are consistent with prior studies of optic neuritis (33), as well as neuroprotective effects mediated by ST266 in a model of traumatic optic neuropathy (36). Importantly, the current results suggest that once daily ST266 dosing is sufficient to promote maximal neuroprotective effects, as twice daily treatment led to equivalent outcomes.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The current studies demonstrated that intranasal delivery of the novel biologic therapy ST266 promoted beneficial effects on multiple features of experimental optic neuritis, including attenuating vision loss, promoting RGC survival, and reducing the degree of optic nerve inflammation and demyelination. Results are consistent with prior studies of optic neuritis (33), as well as neuroprotective effects mediated by ST266 in a model of traumatic optic neuropathy (36). Importantly, the current results suggest that once daily ST266 dosing is sufficient to promote maximal neuroprotective effects, as twice daily treatment led to equivalent outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…ST266 (Noveome Biotherapeutics, Inc., Pittsburgh, PA) was aliquoted and stored at −20 °C. A fresh aliquot was thawed and warmed to room temperature each day and administered to the mice as a single 6 μL drop placed in the nose (33,36). Mice were grouped and treated once or twice with one drop of ST266, PBS, STM100 (the cell culture medium used to culture AMP cells and collect ST266 protein secretions), or 0.5% human serum albumin (HSA) in PBS intranasally beginning after the onset of optic neuritis (day 15 postimmunization).…”
Section: St266 Treatmentmentioning
confidence: 99%
“…Intranasal administration of the secretome from multipotent stem/progenitor cells has been proposed as a strategy for treating other diseases, such as retinal ganglion cell loss [ 75 , 76 ], multiple sclerosis [ 77 ], Alzheimer’s disease [ 78 ], and Parkinson’s disease [ 79 ], including recently, alcohol and nicotine consumption [ 58 ]. In all these models, MSC-S has shown anti-inflammatory and antioxidant effects, also improving neurodevelopment and memory function.…”
Section: Discussionmentioning
confidence: 99%
“…Intranasally-delivered ST266 protects against vision loss, preserves retinal ganglion cells (RGCs), and decreases inflammation and demyelination of the optic nerve in the experimental autoimmune encephalomyelitis (EAE) mouse model of MS [ 4 , 6 ]. These effects are selective for EAE optic neuritis, with the highest concentrations of ST266 proteins accumulating preferentially in the eye and optic nerve, with no effects observed in suppressing EAE lesions in the spinal cords of the same mice [ 4 ].…”
Section: Introductionmentioning
confidence: 99%